Hiperglicemia al ingreso como factor pronóstico de gravedad en pacientes con COVID-19 - Castro Cóndor, Mayra Alejandra (2022)
To determine the association between hyperglycemia on admission and severity in hospitalized patients for COVID-19. Materials and Methods: Retrospective observational design, a sample was taken of 1092 patients seen in the study period and who met the established inclusion and exclusion criteria. Those patients with a diagnosis of COVID-19 confirmed by rapid or molecular tests were included and hyperglycemia was considered when the blood glucose level was> 180 mg / dl in a measurement within the first 24 hours. For data analysis, Microsoft Excel 19 and SPSS programs were used. Results: Of the 1092, 14.4% had hyperglycemia on admission and 85.6% had normoglycemia on admission. Of the total of patients with hyperglycemia, 78.5% presented complications, while 21.5% did not present complications. Of the total number of patients, 56% presented complications, of these, 20.2% also presented hyperglycemia and 79.8% did not present hyperglycemia. The complication rate was significantly higher in hyperglycemic patients (78.5%) compared to non-hyperglycemic patients (52.2%). Conclusions: Hyperglycemia on admission is a prognostic factor for severity in COVID-19 patients.